Transcriptional changes and developmental abnormalities in a zebrafish model of myotonic dystrophy type 1 - Peter K. Todd; Feras Y. Ackall; Junguk Hur; Kush Sharma; Henry L. Paulson; James J. Dowling (The Company of Biologists, 2014)
Myotonic dystrophy type I (DM1) is a multi-system, autosomal dominant disorder caused by expansion of a CTG repeat sequence in the 3'UTR of the DMPK gene. The size of the repeat sequence correlates with age at onset and disease severity, with large repeats leading to congenital forms of DM1 associated with hypotonia and intellectual disability. In models of adult DM1, expanded CUG repeats lead to an RNA toxic gain of function, mediated at least in part by sequestering specific RNA splicing proteins, most notably muscleblind-related (MBNL) proteins. However, the impact of CUG RNA repeat expression on early developmental processes is not well understood. To better understand early developmental processes in DM1, we utilized the zebrafish, Danio rerio, as a model system. Direct injection of (CUG)91 repeat-containing mRNA into single-cell embryos induces toxicity in the nervous system and muscle during early development. These effects manifest as abnormal morphology, behavioral abnormalities and broad transcriptional changes, as shown by cDNA microarray analysis. Co-injection of zebrafish mbnl2 RNA suppresses (CUG)91 RNA toxicity and reverses the associated behavioral and transcriptional abnormalities. Taken together, these findings suggest that early expression of exogenously transcribed CUG repeat RNA can disrupt normal muscle and nervous system development and provides a new model for DM1 research that is amenable to small-molecule therapeutic development.